2015
DOI: 10.1063/1.4935342
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced memory characteristics in organic ferroelectric field-effect transistors through thermal annealing

Abstract: We report on the memory characteristics of organic ferroelectric field-effect transistors (FeFETs) using spin-coated poly(vinylidene difluoride/trifluoroethylene) (P(VDF/TrFE)) as a gate insulating layer. By thermal annealing the P(VDF/TrFE) layer at temperatures above its melting point, we could significantly improve the on/off current ratio to over 104. Considerable changes in the surface morphology and x-ray diffraction patterns were also observed in the P(VDF/TrFE) layer as a result of the annealing proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Next, a solution of P(VDF‐TrFE) was spun onto the substrate to form the ferroelectric layer (200 nm in thickness). Subsequently, the film of the P(VDF‐TrFE) was annealed at 135 °C for 1 h in ambient air in order to increase its crystallinity . Next, DNTT was deposited onto the ferroelectric layer by thermal deposition (75 nm in thickness).…”
Section: Methodsmentioning
confidence: 99%
“…Next, a solution of P(VDF‐TrFE) was spun onto the substrate to form the ferroelectric layer (200 nm in thickness). Subsequently, the film of the P(VDF‐TrFE) was annealed at 135 °C for 1 h in ambient air in order to increase its crystallinity . Next, DNTT was deposited onto the ferroelectric layer by thermal deposition (75 nm in thickness).…”
Section: Methodsmentioning
confidence: 99%
“…Data computation has become increasingly essential in the modern world and is the backbone of various technologies such as the internet of things (IoT), big data, artificial intelligence materials in the FeFET architecture. [14][15][16] Among them, AOS has attracted special attention as an active channel layer material due to various advantages such as its remarkable electrical properties, high transparency, and decent stability. [17] Lee et al reported amorphous silicon-zinc-tin-oxide (a-SZTO) as an AOS thin-film transistor with better electrical performance and good stability.…”
Section: Introductionmentioning
confidence: 99%
“…P(VDF-TrFE) has been applied to several devices such as pressure sensors, memories, and actuators. [15][16][17][18][19][20] In particular, printed pressure sensors based on the P(VDF-TrFE) can be expected to be applied to health-care devices because of their high sensitivity to pressure. 21) Moreover, P(VDF-TrFE) is compatible with the printing process because of its solubility in several organic solvents.…”
Section: Introductionmentioning
confidence: 99%